Putusan Mahkamah Konstitusi Menghapus Rintisan Sekolah Bertaraf Internasional dalam Tinjauan Maqashid Syari’ah - Suhaeri, Suhaeri (Mahkamah Konstitusi Republik Indonesia, 2013)
Article 50 paragraph(3) of Law No. 20 of 2003 on National Education Systems that reads “Government and / or local government orgsnizes at least one education unit on all levels of education to be developed as an international strandard educational system. ”On Tuesday, 8 January 2013, Constitutional Court (MK) declared that the article no longer has binding force of law. With this MK’s verdict it is therefore clear that International-Standard Pilot Project School (RSBI) and International-Standard School (SBI) will shortly be abolished from our national education system since it is in opposition to the 1945 Constitution. Constitutional Court’s decision that abolishes RSBI is interesting because RSBI is actually expected to be the benchmark for the success of educational development. An RSBI that is established in a district serves as a model for other schools. Those schools also develop to be international-standard schools. In other words, RSBI is established to improve quality of education. Then why shouldbeabolished? Is the Constitutional Courtdecision right? Thesesarethe research question which become the subject matter of this writing. Maqashid Syari’ah method is used to find out the answer to the questions. Based on the analysis of Maqashid Syariah on the Court’s decision, the research came to a conclusion that the Ministry of education with its RSBI has higher level of mashlahat(benefit/advantage) than that of Constitutional Court’s. Moreover, in today’s global context, the Constitutional Court decision that abolished RSBI is considered inappropriate.